The relationship between the incidence of couvade syndrome and prenatal paternal attachment in prospective fathers and the affecting factors - Kucukkaya, Burcu; Isik, Hafsa Kubra (Bmc, 2025)
Background Couvade Syndrome (sympathetic pregnancy) is an involuntary disorder in which the prospective father experiences unexplainable physiological and/or psychological symptoms in the transition period to parenthood. This study aimed to determine the relationship between the incidence of Couvade syndrome and prenatal paternal attachment in prospective fathers living in Turkey and the influencing factors. Methods This cross-sectional study was conducted with 486 prospective fathers by simple random method through a web-based questionnaire distributed through social media and communication platforms (Facebook, Instagram, Telegram, or WhatsApp etc.) between May and August 2023. A Participant Identification Form and the Prenatal Paternal Attachment Scale were used to collect the data. Since there is no scale that quantitatively evaluates Couvade syndrome, Couvade syndrome was evaluated on the basis of symptoms through the Personal Information Form created by reviewing the literature. Logistic regression analysis was used to determine correlations between variables and scale scores. Results It was determined that 89.3% of the participants experienced at least three of the pregnancy-related complaints (such as weight gain, nausea, vomiting, edema, leg pain) during their spouse's pregnancy. It was determined that the most frequently experienced symptoms by the prospective fathers were weight gain (59.1%), changes in sleep pattern (59.8%), increased stress (56.7%), and nausea (50.6%). The participants' mean score on Prenatal Paternal Attachment Scale was 43.98. In the study, a statistically significant difference was found between prenatal paternal attachment levels and weight gain, loss of appetite, sensitivity to smells, changes in sleep patterns, financial worries, increased stress, and experiencing food craving (p < 0.001). Among the significant predictors related with Couvade syndrome were educational status, income status, employment status, spouse's educational and employment status, parity and live births, infant's gender, and planned pregnancy status (p < 0.001). In addition, experiencing Couvade syndrome according to their spouses' pregnancy periods is also among the important predictors (p < 0.01). Conclusion In the study, it was seen that prenatal paternal attachment levels of the fathers was high. Couvade syndrome characteristics were found to affect prenatal paternal attachment levels.
Keywords: Couvade Syndrome; Prenatal Attachment; Prospective Fathers; Affecting Factors; Frequency